Health Seeking Behaviour and Health Related Quality of Life among Dyspeptic Students of a Tertiary Institution in Ekiti State, Nigeria - Solomon, Abidemi; Solomon, Ayomikun; Aina, Olukayode; Agbesanwa, Anthony; Owoyemi, Ayodeji; Olusola, Emmanuel; Jolayemi, Olalekan (Global Journal of Health Sciences, 2025)
Purpose: Dyspepsia is a common medical presentation especially in primary care with great impact on the quality of life of those affected with accompanied higher utilization of healthcare resources during investigations and treatment. Dyspepsia symptoms interfere with daily activities, with significant effect on quality of life, necessitating urgent need for the sufferers to seek relief either within established healthcare set up or other avenues. This study set out to observe health seeking behaviour and health related quality of life among dyspeptic students of a tertiary institution of Ekiti state. Methodology: A descriptive and cross-sectional study among the students of Ekiti State University (EKSU). Students aged 16 and above who consented and were not acutely or chronically ill were randomly selected for the study, while those who were pregnant or showed signs of hepatic or pancreatic disease (such as yellow eyes) were excluded. Data were analyzed with IBM SPSS version 26. Main outcome measures in this study were the prevalence of uninvestigated dyspepsia, pattern of treatment practises of respondents when they had dyspepsia, the effect of dyspepsia on the quality of life of the respondents by Short Form of Nepean Dyspepsia Index (SF-NDI). Results were shown as proportions and means with 95% confidence; the P value was 0.05. Bivariate analysis of dyspeptic and non-dyspeptic groups association with health-related quality of life determined with Chi Square, Findings: Three hundred and sixty-four respondents were enrolled. Dyspepsia was present among 169, 46.4% of the respondents. There was significant poor health seeking behaviour among the respondents with dyspepsia as 70 (41.4%) did nothing when they experienced dyspepsia and 64.6% reported significant reduction in health-related quality of life which was worse in the tension and anxiety subdomains. Unique Contribution to Theory, Practice and Policy: This study observed high prevalence of uninvestigated dyspepsia among the undergraduates with associated significant poor health seeking behaviour, and significant reduction of health-related quality of life, worse within the psychological domain. We recommend health education about dyspepsia and other chronic medical conditions among undergraduates during their enrolment in the university’s healthcare system.